2006
DOI: 10.1007/s10452-006-9049-z
|View full text |Cite
|
Sign up to set email alerts
|

Making water flow: a comparison of the hydrodynamic characteristics of 12 different benthic biological flumes

Abstract: Flume tanks are becoming increasingly important research tools in aquatic ecology, to link biological to hydrodynamical processes.There is no such thing as a ''standard flume tank'', and no flume tank is suitable for every type of research question. A series of experiments has been carried out to characterise and compare the hydrodynamic characteristics of 12 different flume tanks that are designed specifically for biological research. These facilities are part of the EU network BioFlow. The flumes could be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…It is a straight recirculating facility, which was designed and built [Dumas, 2004] to study the erosion of sediments and provide a wider bed shear stress range than in the flume already used at the Centre d'Océanologie de Marseille (see for details Jonsson et al [2006]). The overall length of the channel is 13.5 m. Its test section is 8 m long, with a rectangular cross section of 0.6 m width.…”
Section: Methodsmentioning
confidence: 99%
“…It is a straight recirculating facility, which was designed and built [Dumas, 2004] to study the erosion of sediments and provide a wider bed shear stress range than in the flume already used at the Centre d'Océanologie de Marseille (see for details Jonsson et al [2006]). The overall length of the channel is 13.5 m. Its test section is 8 m long, with a rectangular cross section of 0.6 m width.…”
Section: Methodsmentioning
confidence: 99%
“…One is the particle entrainment simulator (PES) designed by Tsai and Lick [4]; the other is flume tank [5]. Among flume tanks, annular flume has been extensively used to investigate various physical, chemical and biological factors which may influence the stability and erodibility of natural cohesive sediments [6][7][8][9][10].…”
mentioning
confidence: 99%
“…Nowell and Jumars (1987) recommended that flumes for use in biological experiments should have a width to depth ratio of at least 5 to 1 in order to reproduce realistic boundary layers. In a recent review, Jonsson et al (2006) concluded that the ratio between the width of the flume and the wall boundary layer thickness (δ) is a more important consideration, recommending that flume width should exceed 2δ + k where k is a relevant length scale of the organism under investigation. Similarly, an ecologist aware of the diel activity and light sensitivity of aquatic insects may question the value of examining the movements of negatively phototactic species on flume beds that are brightly lit or lacking shelter (Barmuta et al, 2001).…”
Section: General Considerations For Interdisciplinary Flume Experimentsmentioning
confidence: 99%
“…Jonsson et al, (2006) recently made a direct comparison of a selection of facilities with the aim of identifying those flumes best suited to the study of benthos-flow interactions in marine environments. In general, however, we are unaware of attempts to define facility protocols or best-practice procedures.…”
Section: Flume Facilities and Hydraulic Measurementsmentioning
confidence: 99%